“Person with disabilities” and their “social determinants of health”- the neglected paradigm of public health - Mohammad Monjurul Karim (Berita Kedokteran Masyarakat (BKM), 2018)
This study was conducted to aware the audience to be more concern about “person with disabilities” and their “social determinants of health” as an emerging area in public health. WHO mentioned, 15% of the global populations are suffering from some form of disabilities and the number is higher comparing the report of 1970s. Public health aim to prevent mortality, morbidity and disability in different sectors (Donald, Lollar & John, 2003). But its alarming that disability preventive program often neglected in public health programs. Even the link between diseases and disability is often overlooked in several cases like GBS, encephalitis, transverse myelitis etc. Reduced inflow and increased outflow of finance and social determinants of health impact negatively on the life of the person with disabilities. Continuous effort to improve the social determinants of health worked tremendously over the last few decades to improve the life of human being globally, which is unfortunately sometimes worked as predisposing factor to the increased number of disabilities. But effort to reduce burden of disability and to improve SDH is just negligible. The 67th World Health Assembly adopted a resolution endorsing the WHO global disability action plan 2014–2021: Better health for all people with disability. It reflects the major shift in global understanding and responses towards disability. It could be concluded that it’s the high time to look more precisely in this neglected area whiting various discourse of SDH which will be a big burden of the public health in coming days. More research is required to minimize number of disability as well the after math of disability.